A CASE OF POLITRAUMA TREATED IN THE ICU OF IASI NEUROSURGERY HOSPITAL - Cristian MARTINIUC; Gheorghe DOROBAT (Romanian Dental Association for Education, 2013)
We present the case of T. A., a 17 years old woman, victim of a scooter accident. The patient was admitted in the ICU in deep coma (Glasgow Coma Scale 5), with politrauma: severe head trauma, left occipital hematoma and laceration, bilateral fronto-temporal haemorragic contusions, double fracture of the mandibula, pulmonary contusion, abdominal trauma, fracture of the left clavicle and distal epiphysis of the left radius bone. The patient suffered multiple neurosurgical operations. She was mechanically ventilated for 10 days and suffered complications such as ARDS, bacterial meningitis and severe sepsis with hospital aquired microorganisms. During the stay in ICU, after an alternating but eventually positive evolution, the rehabilitation therapy was instituted. At discharge, the patient was conscious (GCS - 11), with sensory aphasia and right hemiparesis and was referred to a neurologic rehabilitation clinic.